Meningkatkan Keterampilan Komunikasi Bisnis dan Pembuatan CV untuk Siswa sebagai Persiapan Memasuki Dunia Kerja - Ansori, Ilman; Sumiarsih, Mia; Kusumah, Danial; Hanifa, Nifa; Nisa, Sita Hoerun (LPPM UNIVERSITAS DIAN NUSWANTORO, 2025)
This community service activity aims to enhance business communication skills and Curriculum Vitae (CV) writing for vocational high school (SMK) students as part of their preparation for entering the workforce. In the professional world, the ability to communicate effectively and craft an attractive CV are two crucial aspects that can support career success.The program is designed to provide students with an in-depth understanding of business communication concepts, including the use of polite, effective, and professional language in formal situations. In addition, students receive practical training to create CVs that meet industry standards, highlighting their skills, experiences, and personalities in an appealing and relevant manner.Through a series of activities such as workshops, hands-on training, job interview simulations, and interactive discussions, students will be encouraged to sharpen their communication skills, prepare professional work documents, and boost their confidence when facing the job selection process. This initiative is expected to have a positive impact by better preparing SMK students to face the challenges of a competitive job market.The outcomes of this program include the creation of a professional CV for each participant, increased understanding of business communication, and improved mental and technical readiness for entering the workforce. Thus, this activity can make a significant contribution to supporting the success of SMK students in adapting to the professional world.